Physical Domain of Quality of Life in Premenopause and Post Menopause Women in Central of Java - Marni, Marni; Husna, Putri Halimu (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Abstract. Background: Premenopause and menopause would affect changes in a woman's body. Physical changes during premenopause and menopause would affect a woman's quality of life. Physical changes also caused physical symptoms that were very disturbing in daily activities. This study analyzes the factors that influence physical symptoms on the quality of life of premenopausal and postmenopausal women. Methods: This research method was a descriptive study with a cross sectional study approach. This research was conducted in Central Java province from March to December 2022. The population in this study were premenopausal and postmenopausal women in Central Java. The sampling technique was carried out using the clustered random sampling method. Respondents to this study were taken from 4 districts from 4 corners of Central Java province, namely Kudus Regency, Sukoharjo Regency, Tegal Regency and Semarang Regency. Each district taken 25 respondents. Respondents' quality of life was measured using the Menopause Specific Quality of Life (MENQOL) questionnaire. This study was analyzed using chi square. Results: education, religion, occupation, age at menarche, parity, income, history of illness, current activity, history of sexual intercourse, frequency of sexual intercourse significantly influence the physical domain of quality of life of postmenopausal women with a p-value 0.005. Age, education, occupation, age at menarche, marital status, parity, income, medical history, current activity, history of sexual intercourse, frequency of sexual intercourse significantly influence the physical domain of quality of life of premenopausal women with a p-value 0.005. Conclusion: The physical domain of quality of life for postmenopausal and premenopausal women is influenced by the same factors, namely education, occupation, age at menarche, parity, income, medical history, current activity, history of sexual intercourse, and frequency of sexual intercourse. Physical symptoms in postmenopausal women are in the mild category, while premenopausal women have severe physical symptoms